REALISASI PENERIMAAN PAJAK RESTORAN DITINJAU DARI ANALISIS POTENSI DAN EFEKTIVITAS PEMUNGUTAN PAJAK RESTORAN DI KABUPATEN BADUNG - Gde Herry Sugiarto Asana; Ni Made Christine Dwiyanti; Ni Kadek Liang Nanda Lestari (Journal of Applied Management and Accounting Science, 2022)
The purpose of this study was to determine the potential and effectiveness of restaurant tax collection in Badung Regency. The number of samples from each district was calculated using the Slovin formula. Data collection was carried out through surveys, non-participant observation. The analysis technique used is descriptive quantitative. Based on the results of the analysis, it is known that the potential for restaurant tax in Badung Regency in 2019 is quite large and there is still potential that must be explored optimally. The effectiveness of restaurant tax collection in Badung Regency in 2019 is 93 percent with effective criteria. The results of this study contribute to the realization of restaurant tax revenue.